Meningkatkan hasil belajar pendidikan agama Hindu dan budi pekerti siswa kelas XI IPS2 SMA Negeri 1 Marga melalui penerapan teknik megending - I Gusti Ketut Sukarta (Indonesian Journal of Educational Development, 2020)
The purpose of this study was to determine the effectiveness of the magending technique as an effort to improve the learning outcomes of Hindu Religious Education and Characteristics of Class XI IPS2 students in semester 1 of the 2018/2019 academic year. This type of research is classroom action research conducted in the form of cycles consisting of 4 stages: planning, action, observation, and reflection. The research subjects were 37 students of SMA Negeri 1 Marga Class XI IPS2 semester 1 of the 2018/2019 academic year, while the object of the study was the learning outcomes of Hindu Religious Education and Characteristics. Learning outcomes data were collected using learning outcomes tests and analyzed descriptively qualitatively. The success criteria are set as follows: (1) the average value of each test cycle of at least 70 (KKM scores) and (2) completeness class of at least 85%. The study began by conducting initial reflections with the following conditions: students' enthusiasm for learning was very low, the average value in the previous daily tests only reached 64.78, far below the KKM score of 70, and the number of students who completed study was only 26 out of 37 students, so the classical learning completeness reaches only 70.27%. After the action research there was an increase as follows: in the first cycle the average grade had reached 71.52 and the number of students who completed as many as 30 people so that mastery learning reached 81.08%; while in cycle II the average value of the class was 78.45 with the total number of students reaching 34 people, so the classical learning completeness reached 91.89%. Conclusion: the application of the magending technique effectively improves the learning outcomes of class XI IPS2 students of SMA Negeri 1 Marga in the first semester of the 2018/2019academic year. Tujuan penelitian adalah untuk mengetahui keefektifan teknik magending sebagai upaya untuk meningkatkan hasil belajar Pendidikan Agama Hindu dan Budi Pekerti siswa Kelas XI IPS2 semester 1 tahun pelajaran 2018/2019. Jenis penelitian adalah penelitian tindakan kelas yang dilaksanakan dalam bentuk siklus yang terdiri dari 4 tahap yaitu perencanaan, tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa SMA Negeri 1 Marga Kelas XI IPS2 semester 1 tahun pelajaran 2018/2019 berjumlah 37 orang, sedangkan objek penelitian adalah hasil belajar Pendidikan Agama Hindu dan Budi Pekerti. Data hasil belajar dikumpulkan menggunakan tes hasil belajar dan dianalisis secara deskriptif kualitatif. Kriteriakeberhasilan ditetapkan sebagai berikut: (1) nilai rata-rata ulangan setiap siklus minimal 70 (nilai KKM) dan (2) ketuntasan klasikan minmal 85%. Penelitian ini didahului dengan melakukan refleksi awal dengan kondisi sebagai berikut: semangat siswa belajar sangat rendah, nilai rata-rata pada ulangan harian sebelumnya hanya mencapai 64,78 berada jauh di bawah nilai KKM 70, dan jumlah siswa yang tuntas belajar hanya 26 orang dari 37 orang siswa, sehingga ketuntasan belajar secara klasikal baru mencapai 70,27%. Setelah dilakukan penelitian tindakan terjadi peningkatan sebagai berikut: pada siklus I nilai rata-rata kelassudah mencapai 71,52 dan jumlah siswa yang tuntas sebanyak 30 orang sehingga ketuntasan belajar mencapai 81,08%; sedangkan pada siklus II nilai rata-rata kelas sebesar 78,45 dengan jumlah siswa yang tuntas mencapai 34 orang, sehingga ketuntasan belajar klasikal mencapai 91,89%. Simpulan: penerapan teknik magending efektif meningkatkan hasil belajar siswa kelas XI IPS2 SMA Negeri 1 Marga semester 1 tahun pelajaran 2018/2019.